The Urgency of Using al-Milk an-Naqiṣ in Geographical Indications: An Ideal Preservation for Intellectual Property in Indonesia - Saputro, Triyono Adi; Rumadan, Ismail; Suwadi, Pujiyono; Latifah, Emmy; Syaiful, Muhammad (JURIS (Jurnal Ilmiah Syariah), 2024)
This study aimed at explaining the ideal preservation of intellectual property inventions so that geographical indications (GI) products can increase and be highly competitive in the global market. The existence of GI play a vital role in supporting business competition at the national and international trade levels. GI not only provide protection for intellectual property inventions, but also provide legal guarantees of official legality from the government. This study used a conceptual and comparative approach supported by primary legal materials consisting of GI laws combined with texts and fiqh. The research results shows that al-milk an-naqiṣ’s efforts with the al-ibahah type will be an ideal model for preserving GI for intellectual property inventions in Indonesia in the future. This is because al-milk an-naqiṣ, which is varied and implemented in the community, is able to strengthen GI inventions, can last longer, and without any contracts. In addition, there are advantages to be gained by using al-milk an-naqiṣ, such as having different ownership models, no time limit for transferring ownership, and the ability to increase the welfare of the community. For this reason, it is necessary to spread the importance of preserving the al-milk an-naqiṣ model in order to form a legal culture and provide legal protection for intellectual property inventions based on GI so that they will last longer in the market in the future. In addition, this is useful to support the increase of regional per capita income and help reduce unemployment through the implementation of al-milk an-naqiṣ GI products as an ideal solution for the long-term preservation of intellectual property inventions.